2006
DOI: 10.2165/00019053-200624080-00002
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin Analogues for the Treatment of Glaucoma and Ocular Hypertension

Abstract: We conducted a systematic review of economic studies of prostaglandin analogues for the treatment of glaucoma to assess the scope of current cost-effectiveness evidence and its relevance to decision-makers. The literature search retrieved 102 studies published before July 2005; after additional hand searching of conference proceedings, 13 full-text articles and 13 abstracts met the inclusion criteria. The reviewers extracted the key characteristics of each of the economic evaluations, and all studies received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…This can be achieved by using topical and/or oral medications, laser surgery, conventional surgery, or a combination of these therapies [101] . Current health economics studies on glaucoma treatment mostly focus on direct costs of glaucoma drugs, and therefore provide only one component of real glau- coma treatment costs [100,102,103] . The main issue that limits this research in the area of glaucoma treatment is absence of a reliable, transparent and validated long-term effectiveness measure [100] .…”
Section: Clinical Outcomes and Socio-economic Impact Of Glaucomamentioning
confidence: 99%
“…This can be achieved by using topical and/or oral medications, laser surgery, conventional surgery, or a combination of these therapies [101] . Current health economics studies on glaucoma treatment mostly focus on direct costs of glaucoma drugs, and therefore provide only one component of real glau- coma treatment costs [100,102,103] . The main issue that limits this research in the area of glaucoma treatment is absence of a reliable, transparent and validated long-term effectiveness measure [100] .…”
Section: Clinical Outcomes and Socio-economic Impact Of Glaucomamentioning
confidence: 99%
“…A recent systematic review of prostaglandin analogs for the treatment of glaucoma and ocular hypertension found that the current body of medical literature does not satisfy the needs of medical decision makers, in part because of the absence of clinically relevant long-term effectiveness measures. 15 Further follow-up of this population-based cohort could provide these data in a clinical setting.…”
Section: Discussionmentioning
confidence: 92%
“…[36] However, with increasing follow-up (up to 8 years) the difference in costs between surgery and medication may even out. The current economic literature regarding glaucoma treatment is predominantly focused on identifying the short-term direct, particularly the precise quantification of glaucoma drug costs[3537] and provide thus only one component of real-world costs for glaucoma.…”
Section: Needs For Future Researchmentioning
confidence: 99%